New late miocene records of Dasypodidae (Xenarthra, Cingulata) from the Salicas Formation (La Rioja province, Argentina) - Barasoain, Darío Daniel (2021)
Fil: Barasoain, Darío Daniel. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas, Naturales y Agrimensura; Argentina.